2021
DOI: 10.1021/acs.est.1c04269
|View full text |Cite
|
Sign up to set email alerts
|

Fugacity-Based Trophic Magnification Factors Characterize Bioaccumulation of Cyclic Methyl Siloxanes within an Urban Terrestrial Avian Food Web: Importance of Organism Body Temperature and Composition

Abstract: Trophic magnification of cyclic volatile methyl siloxanes (cVMS) in a terrestrial food web was investigated by measuring concentrations of octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) and two reference chemicals within air and biota samples from an avian food web located in a mixed urban–agricultural landscape. Terrestrial trophic magnification factors derived from lipid normalized concentrations (TMFLs) for D5 and D6 were 0.94 (0.17 SE) and 1.1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…For example, estimated biotransformation half-lives of D4 and D5 are substantially shorter than those estimated for several fluorinated substances (Table 2). This is consistent with results of toxicokinetic 52 and food web 53 studies indicating limited biomagnification of D4 and D5 in rodents and birds, likely due to biotransformation. 52 However, knowledge of biotransformation processes is limited in many animals, particularly birds and reptiles, which also underscores the need for additional investigations.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…For example, estimated biotransformation half-lives of D4 and D5 are substantially shorter than those estimated for several fluorinated substances (Table 2). This is consistent with results of toxicokinetic 52 and food web 53 studies indicating limited biomagnification of D4 and D5 in rodents and birds, likely due to biotransformation. 52 However, knowledge of biotransformation processes is limited in many animals, particularly birds and reptiles, which also underscores the need for additional investigations.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…Sorptive capacities or solubilities of substances are a function of temperature; therefore, since body temperatures of endothermic predators (e.g., songbirds) and poikilothermic prey (e.g., earthworms) can vary substantially, the total sorptive capacities of PFAS in these organisms will likewise be different. Hence, when normalizing concentrations of substances to act as proxies for fugacity or chemical activity in organisms, sorptive capacities or distribution coefficients used in eqs or should be determined at the appropriate body temperature of the organism . Usually, body temperature is not considered in the derivation of BMFs and TMFs.…”
Section: Theorymentioning
confidence: 99%
“…In terrestrial food webs, Δ 15 N varies between 2.8 and 4.0 and is somewhat higher than those observed in captive airbreathing animals. To derive an enrichment factor that is specific to the food web that is investigated, Fremlin et al (2020Fremlin et al ( , 2021) used a linear mixed-effects model for estimating Δ 15 N for the terrestrial food web that they studied. This approach may be useful for estimating Δ 15 N from data typically collected in trophic magnification studies.…”
Section: Trophic Magnification Study Designmentioning
confidence: 99%
“…where A f and B f and also A a and B a are regression coefficients and B f and B a are used to determine the TMF f and TMF a as 10 Bf or 10 Ba , respectively. Fremlin et al (2021) carried out both fugacity and chemical activity-based analyses of the trophic distribution of several dimethylcyclosiloxanes, DDT, and PCB153 in a terrestrial, avian food web and found differences between TMFs derived through conventional lipid normalization of concentrations and TMF f ' and TMF a 's. An important consideration for determining terrestrial TMFs, which is further detailed in the Supporting Information, is the temperature of the sample because of large temperature differences that can exist between endothermic animals and the food that endothermic animals consume and the air they breathe.…”
Section: Trophic Magnification Study Designmentioning
confidence: 99%
See 1 more Smart Citation